Determinant of sharia banks profitability in Indonesia: The moderating effect of non performing financing - Darmawati Muchtar; Fahmi Azhari; Iswadi Bensaadi (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2021)
This study aims to analyze the effect of capital adequacy ratio (CAR), operating cost of operating income (BOPO) on profitability and examine the role of non performing financing (NPF) in influencing the relationship between CAR and BOPO on profitability of sharia bank in Indonesia. The data used in this study is a panel data that consisting of 10 sharia banks for the period 2010-2018 with 99 observations. The method of analysis data is multiple regression analysis with random effect model. The results of this study in model one show that BOPO has negative and significantly affects profitability, meanwhile CAR has positive but insignificant effect, while and NPF has negative effect on profitability but insignificant in model two. Furthermore, when NPF interected with CAR shows interesting results, in which CAR has negative and significant effect on profitability, while BOPO is still consistent with negative and significant effect on profitability. This suggests that the NPF moderates the influence of CAR and BOPO on profitability. This implies that increase NPF would decrease the effect of CAR on profitability and the effect of BOPO on profitability would be strangted of syaria bank in Indonesia. Keywords: Capital adequacy ratio; BOPO; non performing financing, profitability